Curriculum Interventions and Pedagogical Approaches for Virtual Care Delivery: A Scoping Review. Issue 1 (February 2023) - Palesy, Debra; Forrest, Gail; Crowley, Margaret E.
The onset of the COVID-19 pandemic has accelerated the adoption of virtual care as a modality for home-based care delivery to individuals and cohorts who might not otherwise have access. While a number of positive outcomes have been reported, rapid growth has occurred without critical consideration of clinician education and training. Little is known about the curricular and pedagogical requirements for educating current and future clinicians in virtual care provision. This review was informed by Arksey and O'Malley's five-stage methodological framework for scoping reviews, first published in 2005. Using a clearly articulated search strategy and reporting process, over 4000 pieces of literature were analysed to inform this review. A final 17 papers were included. Common themes emerging in relation to curricula content include the basics of virtual care, cultural awareness, interprofessional collaboration/training, telepresence, encompassing non-verbal, verbal and environmental considerations, and virtual care clinical skills. Standalone modules are recommended for delivering 'the basics' of virtual care, while the interactive/participative approach is endorsed as an appropriate method of instruction. The reviewed literature reviewed offers a set of core inclusions and pedagogical approaches for a virtual care education program, although these are often mentioned in general terms and are not always well described. Moving beyond the COVID-19 pandemic, virtual care education for current and future clinicians requires a consistent and cohesive approach to curricula and pedagogies. These approaches should be rigorously evaluated as part of a continuous quality improvement process.